Non-steroidal Anti-inflammatory Drugs (NSAIDs) Systemic Use: The Risk of Renal Failure - Bensman, Albert (Frontiers in Pediatrics, 2020)
For the pediatric nephrologist ,the over-the –counter status for NSAIDs is surprising due to their possible harmful side effects : -acute renal failure due mainly to glomerular hypoperfusion which may lead to acute tubular necrosis - acute or chronic interstitial nephritis which may cause chronic renal failure - more rarely in children medullary ischemic injury may lead to acute and chronic papillary necrosis All of them may create electrolyte abnormalities : hyponatremia, hyperkaliemia , renal tubular acidosis ,fluid retention causing hypertension